KONSENTRASI TOTAL SENYAWA ANTOSIANIN EKSTRAK KELOPAK BUNGA ROSELLA (Hibiscus sabdariffa L.) : PENGARUH TEMPERATUR DAN pH - E.K. Hayati; U.S Budi; R. Hermawan (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2012)
Recently, Roselle (Hibiscus sabdariffa L.) has been used for tea. Based on this background, research was conducted with the aims: (1) To determine the rate of anthocyanin degradation heating of the roselle calyx extract (Hibiscus sabdariffa L.), (2) To determine the effects of changes during storage on the stability and total concentration of anthicyanin. This research was conducted by extracting the sample with 2% citric acid. Concentrated extract was used to test the stability upon heating temperature, pH during the storage process for ± 30 days. The results of this study indicate that extracts of roselle calyx (Hibiscus sabdariffa L.) experienced a decrease in concentration at 80°C. The anthocyanin degradation rate followed the equation of r = 0.014T – 1.169 with the lowest concentration of 32.916 mg / L.